2010
DOI: 10.1097/ta.0b013e3181e4ec69
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Distribution of Bullet Head Injuries in Combat Fatalities

Abstract: These findings imply that gun-shot entry wounds to the head are unevenly distributed. A partially bullet-proof protective helmet may prevent a substantial fraction of injuries (and fatalities) without a significant weight addition to the helmet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The mortality was significantly lower in the military DoDTR population (23% vs 41%, P < 0.001). Military patients who survived had a discharge mean GCS of 14 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, 32 (32.7%) of them had a discharge GCS < 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality was significantly lower in the military DoDTR population (23% vs 41%, P < 0.001). Military patients who survived had a discharge mean GCS of 14 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, 32 (32.7%) of them had a discharge GCS < 9.…”
Section: Resultsmentioning
confidence: 99%
“…Pannell et al2 in an analysis of Canadian soldiers killed in Afghanistan, reported GSW were the second leading mechanisms of injury causing death and neurological injury after hemorrhage. Analysis of Israeli Defense Forces combat fatalities during the years 2000 to 2004, the Second Lebanon War (2006), and Operation Cast Lead (2009) reported that GSW to the head comprised a substantial fraction of combat injuries and a major cause of death in the battlefield 3. In a review of 369 United States Special Operations Command battle-injured fatalities, GSW accounted for 39.8% and brain injuries in 31.6% of deaths 4.…”
Section: Discussionmentioning
confidence: 99%
“…Four papers were identified that required translation (French and Russian). Following screening, 10 papers1 2 5 7 11 14 – 18 and two books had pertinent information when analysed 6 8. An internet search identified 24 additional publications, only two of which had pertinent information to those three questions,9 19 and that had not been found in the database searching.…”
Section: Resultsmentioning
confidence: 99%
“…2 In the combat zone, penetrating missile wounds to the head are usually deliberate, not accidental, and can lead to increased mortality and morbidity. 3,4 In this particular case, the event had little to do with war and more to do with competitive sports, civic pride, and subsequent celebration. The local soccer team happened to be the Iraqi national team, playing in Baghdad.…”
mentioning
confidence: 91%